Qualitative and quantitative analysis of the bioactive components of "ginseng-polygala" drug pair against PC12 cell injury based on UHPLC-QTOF-MS and HPLC - Zhengyang Wang; Xiaomeng Sun; Yue Zhao; Liba Ga; Qi Li; Qian Li; Xiaotong Wang; Chunjuan Yang (Frontiers Media S.A., 2022)
Aβ25-35-induced PC12 cells were used as the in vitro injury model to evaluate the effects on PC12 cells after intervention with the "ginseng-polygala" drug pair. The results showed that the drug pair could significantly increase cell activity and reduce the level of reactive oxygen species and the concentration of inflammatory factors to improve the Alzheimer's disease treatment process. Furthermore, to rapidly identify and classify complicated bioactive components of the drug pair, a liquid chromatography with quadrupole time-of-flight mass spectrometry method combined with a molecular network strategy was established. With this strategy, 40 constituents were preliminarily identified and a database of the compounds was successfully established. Among them, 12 compounds of different categories were accurately identified by comparison with reference substances. The content of the aforementioned active components was simultaneously determined by HPLC to control the quality of compatible medicinal materials, and the verification results of the analytical method met the content determination requirements. The results revealed that after compatibility, the content change of the components is not the simple addition of quantity but the comprehensive effect of the two medicines. In conclusion, this study could provide a generally applicable strategy for pharmacological activity, structural identification, and content determination in traditional Chinese medicine and its compatibility.